Зарубіжний досвід дитячого руху кінця ХIХ - початку ХХ ст - Наталя Коляда (Pavlo Tychyna Uman State Pedagogical University, 2014)
У статті розкрито основні напрями розвитку зарубіжного дитячого руху як важливого об'єктивного чинника виникнення в Україні дитячого руху. З'ясовано, що світовий дитячий рух кінця ХІХ - початку ХХ ст. представлений рядом дитячих формувань, різноманітних як за формою, так і за змістом діяльності, як самоорганізованих, так і цілеспрямовано організованих. Автором виокремлено такі основні напрями зарубіжного дитячого руху досліджуваного періоду: патріотичний (військово-патріотичний), культурологічний, соціальний, екологічний (натуралістич-ний), скаутський та ін. Дитячий рух став помітним соціокультурним явищем у багатьох країнах світу, що не лише відображало тенденції суспільного розвитку, а й стало значним стимулом розвитку науки і практики виховання. В статье раскрыты основные направления развития зарубежного детского движения как важного объективного фактора возникновения детского движения в Украине. Выяснено, что мировое детское движение конца XIX - начала ХХ в. представлено рядом детских формирований, различных как по форме, так и по содержанию деятельности, как самоорганизующихся, так и целенаправленно организованных. Автором выделены следующие основные направления зарубежного детского движения исследуемого периода: патриотическое (военно-патриотическое), культурологическое, социальное, экологическое (натуралистическое), скаутское и др. Детское движение стало заметным социокультурным явлением во многих странах мира, которое не только отражало тенденции общественного развития, а стало значительным стимулом развития науки и практики воспитания. The main directions of foreign children's movement development as an important objective factor of children's movement arising had been revealed in the article. Forms of self-organization of children's social activity, process of social and educational cooperation of equivalent subjects of social action (children and adults) for the socialization, social education, social and educational support of the child, his rights protection, development of interests, implementation of plans etс. had been described in the children's movement context. The author distinguished the following main directions of studied period foreign children's movement as: patriotic (military-patriotic) - children and youth structures, oriented to training boys to defend the independence of their country, «Boys Brigade» (Scotland), «School battalions» (France), «Union of Young Motherland Defenders» (Germany), «Association of Boys' Skills», «League of Boys Empire» (England), «Church Boys Brigades», «Jewish Boys Brigades», «Society of Falcons» (Czech Republic), «Catholic Boys Brigades» (Europe); cultural - movement of high school students «Migratory Birds» (Germany, the beginning of the 20th century), from which in 1911 the children and youth organization «Union of Young Germany» which promoted a military revival of the country had been established; social - amateur school and out-ofschool «savings banks», «mutual aid societies» («National Union of School Mutual Aid Societies» founded in 1906 in France); environmental (naturalistic) - «May Unions» that at the beginning of the 20th century had spread in Germany, Switzerland, and later in Russia; scout - one of the most striking examples of the global children's movement origin. That group included both directly Scout Associations (educational system «scouting» was founded in England in 1899), and a number of children's groups of early 20th century. Those groups had been acting on the scout basis: children's groups of «Forest Indians», unions «Sons of Daniel Boone», «Boys Pioneers of Dan Byrd» etc. It was found that children's movement had become a prominent social and cultural phenomenon in many countries, reflecting not only the tendencies of social development, but had become a significant stimulus for the development of science and practice of education.